Cloud-Point Extraction Combined with Liquid Chromatography for the Determination of Ergosterol, a Natural Product with Diuretic Activity, in Rat Plasma, Urine, and Faeces - Dan-Qian Chen; Jun-Min An; Ya-Long Feng; Ting Tian; Xiang-Yang Qin; Ying-Yong Zhao (Journal of Analytical Methods in Chemistry)
Ergosterol from many medicinal fungi has been demonstrated to possess a variety of pharmacological activities in vivo and in vitro. A new method based on cloud-point extraction has been developed, optimized and validated for the determination of ergosterol in rat plasma, urine and faeces by liquid chromatography. The non-ionic surfactant Triton X-114 was chosen as the extract solvent. The chromatographic separation was performed on an Inertsil ODS-3 analytical column with a mobile phase consisting of methanol and water (98 : 2, v/v) at a flow rate of 1 mL/min. The methodology was validated completely. The results indicated good performance in terms of specificity, linearity, detection and quantification limits, precision and accuracy. The method was successfully applied to the pharmacokinetic studies of ergosterol in rats. The results indicate that the ergosterol levels in feces are much higher than those in plasma and urine of the rat.